Differences in scapular upward rotation, pectoralis minor and levator scapulae muscle length between the symptomatic, the contralateral asymptomatic shoulder and control subjects: a cross-sectional study in a Spanish primary care setting. Issue 6 (12th June 2019) - Navarro-Ledesma, Santiago; Fernandez-Sanchez, Manuel; Struyf, Filip; Martinez-Calderon, Javier; Miguel Morales-Asencio, Jose; Luque-Suarez, Alejandro
Abstract : Objective: To determine the potential differences in both scapular positioning and scapular movement between the symptomatic and asymptomatic contralateral shoulder, in patients with unilateral subacromial pain syndrome (SAPS), and when compared with participants free of shoulder pain. Setting: Three different primary care centres. Participants: A sample of 73 patients with SAPS in their dominant arm was recruited, with a final sample size of 54 participants. Primary outcome measures: The scapular upward rotation (SUR), the pectoralis minor and the levator scapulae muscles length tests were carried out. Results: When symptomatic shoulders and controls were compared, an increased SUR at all positions (45°, 90° and 135°) was obtained in symptomatic shoulders (2/3, 98/8, 96°, respectively). These differences in SUR surpassed the minimal detectable change (MDC95) (0, 91/1, 55/2, 83° at 45/90/135° of shoulder elevation). No differences were found in SUR between symptomatic and contralateral shoulders. No differences were found in either pectoralis minor or levator scapulae muscle length in all groups. Conclusions: SUR was greater in patients with chronic SAPS compared with controls at different angles of shoulder elevation.